Editors' Choice—Electrodeposition of Platinum on Titanium Felt in a Rectangular Channel Flow Cell. Issue 2 (1st January 2017) - Arenas, Luis F.; de León, Carlos Ponce; Boardman, Richard P.; Walsh, Frank C.
Abstract : Highly porous platinized titanium substrates are attractive electrode materials for industrial electrochemical processing and electrochemical energy storage. The electrodeposition of platinum on titanium felt was carried out in a divided, rectangular channel flow cell from an alkaline bath without additives. The morphology and spatial distribution of the platinum deposits in the porous material were analyzed using SEM and EDS microscopy in addition to X-ray computed tomography (CT). The electroplated surface area was estimated from the charge transfer current ratio for Ce(IV) reduction and related to a theoretical electrosorbed hydrogen monolayer surface area. The platinized titanium felt showed a significant enhancement of active surface area in comparison to conventional electrode materials. Although platinum was present throughout the porous electrode, CT revealed heterogeneous deposits accumulating in regions near the membrane (during electrodeposition), as a result of the potential distribution in the felt material and flowing electrolyte. Uniform platinum coatings are possible on thin titanium felt under 200 μm thick, by either potentiostatic or galvanostatic electrodeposition.